Maturation of the European sardine Sardina pilchardus under experimental conditions strengthens bioenergetic estimate. (September 2020) - Vagner, Marie; Dessier, Aurélie; Dupuy, Christine; Bustamante, Paco; Dubillot, Emmanuel; Lefrançois, Christel; Réveillac, Elodie; Morinière, Pierre; Lefebvre, Sébastien
Abstract: This study aims at (1) experimentally estimating first sexual maturation of the European sardine S. pilchardus, (2) using the results to calibrate existing bioenergetic models. During the 183 days-experiment, fish growth and body condition were assessed by biometry, and gonads were weighed when present. Age, wet weight and total length at first maturity were estimated at 262 days, 10.79 ± 0.75 g, and 11.26 ± 0.21 cm, respectively. Including these traits in biphasic Von Bertalanffy models did not significantly improve simulations for either length or weight data, meaning that energy allocation was not impacted by these traits. The implementation of the results in the Dynamic Energy Budget (DEB) calibration procedure strengthened the parameter set of the existing model, but resulted in significant changes in the energy allocation. Our results are a first step that will allow the design of new experiments to further quantify maturation and reproduction rates in diverse environmental conditions, consolidating DEB model calibration. Highlights: First sexual maturity is of primary interest to understand fish stock variability. This experiment enabled to strengthen the existing bioenergetic models. This experiment also resulted in significant changes in the energy allocation. This is a significant first step to refine models used for stock management.